ZjFAS2 is involved in the fruit coloration in Ziziphus jujuba Mill. by regulating anthocyanin accumulation - Li, Shipeng; Shen, Yuanyuan; Zheng, Shipei; Zhu, Qihang; Cai, Linfang; Wang, Yian; Zhao, Xusheng (Frontiers in Plant Science, 2023)
Fruit color is one of the most important traits of jujube (Ziziphus jujuba Mill.). However, the differences in the pigments of different varieties of Jujube are not well studied. In addition, the genes responsible for fruit color and their underlying molecular mechanisms remain unclear. In this study, two jujube varieties, namely “Fengmiguan” (FMG) and “Tailihong” (TLH), were considered. The metabolites from jujube fruits were investigated using ultra-high-performance liquid chromatography/tandem mass spectrometry. Transcriptome was used to screen anthocyanin regulatory genes. The gene function was confirmed by overexpression and transient expression experiments. The gene expression was analyzed by quantitative reverse transcription polymerase chain reaction analyses and subcellular localization. Yeast-two-hybrid and bimolecular fluorescence complementation were used to screen and identify the interacting protein. These cultivars differed in color owing to their respective anthocyanin accumulation patterns. Three and seven types of anthocyanins were found in FMG and TLH, respectively, which played a key role in the process of fruit coloration. ZjFAS2 positively regulates anthocyanin accumulation. The expression profile of ZjFAS2 exhibited its different expression trends in different tissues and varieties. Subcellular localization experiments showed that ZjFAS2 was localized to the nucleus and membrane. A total of 36 interacting proteins were identified, and the possibility of ZjFAS2 interacting with ZjSHV3 to regulate jujube fruit coloration was studied. Herein, we investigated the role of anthocyanins in the different coloring patterns of the jujube fruits and provided a foundation for elucidating the molecular mechanism underlying jujube fruit coloration.